53rd AIAA Aerospace Sciences Meeting 2015
DOI: 10.2514/6.2015-0824
|View full text |Cite
|
Sign up to set email alerts
|

Flow Control of Unsteadiness in the Wake of a Turbine Blade

Abstract: Vortex shedding, such as the von Kármán vortex street, leads to higher mixing in the wake and unsteady forces on turbine airfoils. As a result, aerodynamic efficiency decreases and structural stress increases. The objective of the present work is to analyze the unsteadiness formed by vortex shedding at the trailing edge of a turbine vane and to manipulate/control this unsteadiness. The effects of steady injection through a tube at the trailing are studied. A detached-eddy simulation procedure, MBFLO2, is used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition to the studies of the causes and effects of vortex shedding, some efforts on controlling the vortex shedding were also made. Irsch et al 9 found that the wake vortices can be reduced effectively by imposing a steady injection through a tube at the trailing edge, and the most effective results were obtained when the excitation frequency was close to the shedding frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the studies of the causes and effects of vortex shedding, some efforts on controlling the vortex shedding were also made. Irsch et al 9 found that the wake vortices can be reduced effectively by imposing a steady injection through a tube at the trailing edge, and the most effective results were obtained when the excitation frequency was close to the shedding frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Irsch et al [175] found that, in the case of a turbine blade, the optimum position for the injection tube is slightly on the blade pressure side at the trailing edge. The injection results in the reduced strength of the vortex oscillations, smaller vortices, and reduced total pressure loss.…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%
“…. +0.15% + + [170] 2016 Recirculating slots AC 7.4-8.4% +2% +10% [174] 2016 Recirculating slots AC −2.71% +33.05% [169] 2015 Grooves CC ±0% +2.48% + [192] 2015 Injection nozzle CC 1.5% +37% [193] 2015 Injection nozzle CC 1-12% +30% [175] 2015 Injection tube Turbine blade 323,955 0.3-4% Reduction in total pressure loss [194] 2015 Recirculating slots AC − − +5.7% [195] 2013 Recirculating holes CC −1% −2% +10% [196] 2013 Recirculating slots CC 11% ±0% +20% [197] 2013 Recirculating slots CC −1% +17% [197] 2013 Recirculating slots with vanes CC +2% +4% + [198] 2012 Recirculating slots CC up to 13% ±0% + [198] 2012 Recirculating slots with vanes CC up to 17% ±0% + [173] 2012 Recirculating slots CC + [199] 2011 Recirculating holes CC −2 . .…”
Section: Injection Suction and Recirculationmentioning
confidence: 99%